Islamic New Public Management Model for Excellent Service in Government Institutions - Masruroh, Nikmatul; Zahra, Halimatus; Rahayu, Nurul Widyawati Islami; Sami, Muhammad (UIN Siber Syekh Nurjati Cirebon, 2026)
Introduction: The service of an institution is a measure of public satisfaction with employee performance. Therefore, service innovation is needed to keep customers happy and coming back. In addition, public service is crucial in government because the public needs confidence in receiving service. This study aims to explore the practice of excellent service in government institutions, analyze the new public management model in government services, examine the Islamic values embedded in the new public management in government services, and develop an Islamic new public management model for government services.Methods: This study used a qualitative case study approach. The case studied here was the presence of one-stop service at the Investment and One-Stop Integrated Services Agency in Jember Regency. The selection of research subjects was purposive, with informants selected based on criteria directly related to the one-stop service model. Data were collected through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model technique and tested through source triangulation. Results: This study found several points. First, excellent service delivery drives digital transformation, enabling licensing services to be completed faster: previously, 1 week to 1 month; after the transformation, only 1 day. The innovation was to make the licensing service a one-stop service. Thus, employee performance was maximized because the public does not need to move from one location to another for licensing. Second, the new public management model being implemented was to present the OSS (Online Single System) service. Third, Islamic values that were present in the practice of new public management, namely the value of siddiq (honesty), which was in the form of transparency, the value of amanah (integrity), which was the commitment of employees, fathonah (smart), which was innovative and creative, the value of discipline, and the value of efficiency. Fourth, the Islamic new public management model was proposed to deliver excellent service, namely by integrating Islamic values into service, so that service is not only technology-based but also ethics-based.Conclusion and suggestion: Digital transformation in the licensing office, through a one-stop model, maximizes employee performance and positively impacts public satisfaction.